Use of portable gamma spectrometers for triage monitoring following the intake of conventional and novel radionuclides. (August 2020) - Medici, Siria; Carbonez, Pierre; Damet, Jérôme; Bochud, François; Pitzschke, Andreas
Abstract: Current internal dosimetry monitoring programmes generally feature periodic measurements that are defined for the most commonly-encountered radionuclides. These programmes are not directly applicable to research centres that produce novel and short-lived radionuclides which are then used for the manufacture of radiopharmaceuticals, such as the CERN-MEDICIS facility hosted at CERN. This work presents an in vivo internal dosimetry programme based on the concept of triage monitoring. The programme allows to comply with the annual committed effective dose limit of E 50 = 1 mSv by performing rapid gamma-spectroscopy screening measurements. Two portable spectrometers (HPGe- and NaI-based) were characterised using two different phantoms: a simplified model of the human torso and an anthropomorphic phantom allowing for customised source-filling geometries. The efficiencies of the spectrometers were determined using both phantoms and the minimum detectable activities were computed as a function of the measuring time for a selection of 21 among novel and conventional radionuclides. The minimum detectable activity was then used to calculate the minimum committed effective dose associated to each measurement for a realistic intake scenario. For a single screening measurement of 30 s performed at the end of the working day, the minimum detectable committed effective dose resulting from a radionuclide inhalation ranged between few μ Sv and hundreds of μ Sv for the majority of the considered radionuclides. The suggested approach allows to set up pragmatic in vivo measurements to monitor the workers' internal contamination in research centres and industries where unsealed conventional and/or novel radionuclides may be handled. Highlights: An approach for internal monitoring of novel and common radionuclides is presented. Screening measurements with two portable gamma spectrometers are considered. Minimum detectable activities are given for two phantoms for several measuring times. Minimum detectable committed dose : tens–hundreds of μ Sv (6 h after intake).